Modern Solutions to Old Problems: A Review of Emerging Digital Technologies in Post-stroke Neurorehabilitation - Matczak, Simon; Namysł, Maria; Woźniak, Kinga; Bieniek, Maciej; Dachowska, Sandra; Haraj, Jan; Sobkowiak, Marcin; Fałczyńska, Aleksandra (Journal of Education, Health and Sport, 2026)
Introduction. Stroke is one of the leading causes of chronic disability worldwide. Conventional rehabilitation frequently faces challenges regarding accessibility, high costs, and difficulties in sustaining patient motivation. These constraints often lead to insufficient training intensity, thereby limiting therapeutic efficacy. Consequently, exploring alternative therapeutic solutions is necessary to enhance clinical outcomes. Aim. This review evaluates the effectiveness of Virtual Reality (VR), Augmented Reality (AR), Robotic-Assisted Training (RAT), and telerehabilitation in post-stroke recovery. Methods. A search of PubMed, Web of Science, and Google Scholar was conducted. Included were randomized controlled trials, systematic reviews, and meta-analyses examining digital technologies in neurorehabilitation. Results. VR and AR improve motor and cognitive functions via immersive feedback. RAT proves effective in delivering high-intensity practice, particularly for lower limb mobility in severe cases, though its superiority over conventional therapy for upper limbs remains inconclusive. Telerehabilitation offers accessibility comparable to face-to-face therapy but relies heavily on patient adherence. Conclusions. Digital technologies address traditional limitations by enabling high-dosage, engaging training that facilitates functional recovery. Future research should focus on optimizing protocols and integrating these solutions into long-term plans.